Urban Farming: Empowerment to Increase Economic, Education, and Nutritional Benefit for the Sub-Urban Community - Nasruddin, Nasruddin; Dwiyantama, Yusuf Donner; Muhammad, Banu; Bowalaksono, Anom; Ayubi, Dian; Pertiwi, Sarah Islamiati (ASEAN Journal of Community Engagement, 2022)
This article discusses the urban farming program at Sekolah Master in Beji, Depok, Indonesia, which aims to provide the community with broader benefits, such as economy, education, and increased nutritional value. The project involves planting method that was introduced to this school community. The program itself consists of several stages, starting from the preparation—dissemination of the program and designing a plan for the greenhouse, the implementation—constructing the greenhouse and installing the automatic water system, planting the vegetation, and monitoring and evaluation of the program. Eventually, an evaluation of the successful program is required to determine whether the program can be implemented in the following year. As a result of the evaluation, the program has succeeded in completing several objectives. The urban farming program has also benefited the community through the natural science education program and also increasing nutritional value. Therefore, such programs should be continued in the following years so that the impact can be broader and more progressive.